Analisis K-Means Clustering untuk Pengelompokan Produksi Padi di Provinsi Aceh Tahun 2025 - Syaubari Syaubari; Ilyas Ilyas; Bavitra Bavitra (Jurnal Industri dan Inovasi (INVASI), 2026)
Indonesia is an agricultural country that makes rice (Oryza sativa L.) as a major food commodity. Aceh Province is one of the rice-producing regions in Indonesia with varying levels of production in each district/city. This study focuses on the grouping of rice-producing districts/cities in Aceh Province using the K-means clustering method by utilizing two variables, namely the harvested area of rice plants and rice production using 3 clusters for 23 districts in Aceh. The results show that there are 8 districts in cluster 1, 11 districts in cluster 2, and 4 districts in cluster 3. Cluster 3, which consists of 4 districts, is a group of districts with the highest harvested area and rice production compared to other districts/cities in Aceh province.